Ovarian activity regulation by anti-Müllerian hormone in early stages of human female life, an overview - Jusiakowska-Piputa, Małgorzata; Kaczmarek, Maria (Anthropological Review, 2018)
The present study aimed at describing the anti-Müllerian hormone (AMH), with special focus on molecular background for ovarian activity, in particular the role AMH plays in sex determination and gonadogenesis process in early stages of prenatal life and folliculogenesis in postnatal life. It is a review of the literature currently indexed and abstracted in MEDLINE, SCOPUS and Google Scholars. The process of sex determination and gonad differentiation occurring during embryogenesis was discussed along with underlying molecular mechanisms. In the postnatal life the impact of AMH on the process of folliculogenesis was described. Clinical use of recent findings was shown as well. Genetic studies and molecular analyses have demonstrated that AMH is highly conservative, indicating its significance in reproductive process on the background of evolutionary processes.